The natural style. Issue 3 (3rd July 2018) - Pettersson, Rune
Abstract: The medieval Franciscan friar Roger Bacon realized that paintings in churches did not illustrate the stories in the Bible in a natural and realistic way. According to Bacon such paintings should be illustrative in a natural style and tell us about the holy texts in a clear way. An important step towards illustrative images emerged in the late frescoes in the Papal Basilica of Saint Francis of Assisi (1297–1300). Roger Bacon's natural style was widely spread. The medieval painter Giotto worked with an extensive series of murals in the Scrovegni Chapel in Padua, dedicated to the Blessed Virgin. Giotto and his team of about 40 collaborators covered the entire surface of the walls and the ceiling of the building with fresco paintings (1303–1305). For the first time since ancient times, painted figures appeared as living, natural people. These frescos are often regarded as a turning point in Western art history. We can see Giotto as an early information designer, more than 700 years ago.